Long-Term Radiographic and Clinical Outcomes in Patients Undergoing Transforaminal Endoscopic Lumbar Discectomy: A Propensity Score Matching Study - Mu G; Yue L; Sun H (Journal of Pain Research, 2023)
Guanzhang Mu,* Lei Yue,* Haolin Sun Orthopaedic Department, Peking University First Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haolin Sun, Orthopedic Department, Peking University First Hospital, 8th Xishiku Ave, Beijing, 100034, People’s Republic of China, Tel +86-1083572655, Email sunhaolin@vip.163.comBackground: Our study aims to investigate the long-term clinical and radiographic effects of transforaminal endoscopic lumbar discectomy (TELD) on lumbar disc herniation.Patients and Methods: Radiographic and clinical data of patients undergoing TELD in our institution from January 2015 to January 2019 were retrospectively collected. LDH outpatients who had not received surgical treatment during the same period were 1:1 matched by propensity score matching as the conservative group. The radiographic parameters of the two groups at baseline and at the last follow-up (≥ 24 months) were analyzed.Results: The study included 47 patients in the TELD group, matched with 47 patients in the conservative group. The disc height of the TELD group at the last follow-up was lower than that at the baseline (P < 0.001), and lower than that of the conservative group at the last follow-up (P < 0.05). The disc degeneration grade of the TELD group at the last follow-up was greater than that at the baseline, and greater than that of the conservative group at the last follow-up. There was no significant difference in the facet joint degeneration in the TELD group between the baseline and the last follow-up, and between the TELD group and the conservative group at the last follow-up (P > 0.05). The pain intensity and disability score in the TELD group at 3-month follow-up and at the last follow-up were significantly lower than those at the baseline (P < 0.001). Six patients in the TELD group required additional surgery during the follow-up period.Conclusion: Our long-term follow-up data shows that the disc height of the operated level was significantly reduced and the disc degeneration was significantly aggravated in TELD-treated patients; in contrast, the facet joint degeneration did not show significant aggravation.Keywords: endoscopic discectomy, spinal surgery, minimally invasive, lumbar disc herniation